PERJANJIAN KERJA BERSAMA (PKB) DI PT.PAMA PERSADA NUSANTARASANGATTA KABUPATEN KUTAI TIMUR - Murwanto, Fl. Sudiran Sugeng (PREDIKSI, 2016)
He purpose of this study was to find out the Collective Labor Agreement (CLA) which took place at PT. Pama Persada Nusantara KPCS Sangatta District. The timing of the research conducted in January 2016 through May 2016 for five(5) months.The research method in this research is descriptive qualitative research about the role of the Collective Labour Agreement (CLA) in PT. Pama Persada Nusantara KPCS Sangatta District. The collection of data by distributing questionnaires, observation and interviews.The study states that the Collective Labour Agreement (CLA) made between employees and the company has been running well in the PT. Pama Persada Nusantara Sengata KPCS district, the Collective Labor Agreement (CLA) function ensures a mutually beneficial relationship both parties to regulate the rights and obligations of the parties there.